The climate of the Common Era off the Iberian Peninsula - Abrantes, Fatima (2018)
The Mediterranean region is a climate hot spot, sensitive not only to global warming but also to water availability. In this work we document major temperature and precipitation changes in the Iberian Peninsula and margin during the last 2000 years and propose an interplay of the North Atlantic internal variability with the three atmospheric circulation modes (ACMs), (North Atlantic Oscillation (NAO), east atlantic (EA) and Scandinavia (SCAND)) to explain the detected climate variability. We present reconstructions of sea surface temperature (SST derived from alkenones) and on-land precipitation (estimated from higher plant n-alkanes and pollen data) in sedimentary sequences recovered along the Iberian Margin between the south of Portugal (Algarve) and the northwest of Spain (Galiza) (36 to 42 degrees N). A clear long-term cooling trend, from 0 CE to the beginning of the 20th century, emerges in all SST records and is considered to be a reflection of the decrease in the Northern Hemisphere summer insolation that began after the Holocene optimum. Multi-decadal/centennial SST variability follows other records from Spain, Europe and the Northern Hemisphere. Warm SSTs throughout the first 1300 years encompass the Roman period (RP), the Dark Ages (DA) and the Medieval Climate Anomaly (MCA). A cooling initiated at 1300 CE leads to 4 centuries of colder SSTs contemporary with the Little Ice Age (LIA), while a climate warming at 1800 CE marks the beginning of the modern/Industrial Era. Novel results include two distinct phases in the MCA: an early period (900-1100 years) characterized by intense precipitation/flooding and warm winters but a cooler spring-fall season attributed to the interplay of internal oceanic variability with a positive phase in the three modes of atmospheric circulation (NAO, EA and SCAND). The late MCA is marked by cooler and relatively drier winters and a warmer spring-fall season consistent with a shift to a negative mode of the SCAND. The Industrial Era reveals a clear difference between the NW Iberia and the Algarve records. While off NW Iberia variability is low, the Algarve shows large-amplitude decadal variability with an inverse relationship between SST and river input. Such conditions suggest a shift in the EA mode, from negative between 1900 and 1970 CE to positive after 1970, while NAO and SCAND remain in a positive phase. The particularly noticeable rise in SST at the Algarve site by the mid-20th century (+/- 1970), provides evidence for a regional response to the ongoing climate warming. The reported findings have implications for decadal-scale predictions of future climate change in the Iberian Peninsula.